Mountain mistletoe Christmas - Johns, Patricia (Romance writer) (Johns, Patricia (Romance writer). Second chance club., 2020)
Can the magic of the season... bring opposites together? Don't change for a relationship. That's contractor Nick Bryant's motto. But when single mom Jen Taylor hires him to renovate her old mansion, he wants to impress her. Nick knows Jen's focus is her son, and she'll never want a man who wields a hammer instead of a Harvard degree. But as they prepare her home for Christmas, he can't help wishing for a moment under the mistletoe!